Survival and morbidity in very preterm infants in Shenzhen: a multi-center study - Li, Tingting; Zhang, Guofei; Li, Rui; He, Shengnan; Zhang, Fangshi; Yan, Xudong; Yu, Zhangbin; Xie, Yingmei; , Shenzhen Neonatal Data Network; Zhong, Guichao; Chen, Cheng; Zhuang, Xueling; et al. (Frontiers in Pediatrics, 2024)
To analyze survival and morbidity among very preterm infants (VPIs) in Shenzhen and explore factors associated with survival without major morbidity.Methods: Between January 2022 and December 2022, 797 infants were admitted to 25 neonatal intensive care units in Shenzhen with gestational age (GA) <32 weeks, excluded discharged against medical advice, insufficient information, and congenital malformation, 742 VPIs were included. Comparison of maternal and neonate characteristics, morbidities, survival, and survival without major morbidities between groups used Mann Whitney U test and X 2 test, multivariate logistic regression was used to analyze of risk factors of survival without major morbidities.The median GA was 29.86 weeks (interquartile range [IQR], 28.0-31.04), and the median birth weight was 1250 g (IQR, 900-1500). Of the 797 VPIs, 721 (90.46%) survived, 53.52%(38 of 71) at 25 weeks' or less GA, 86.78%(105 of 121) at 26 to 27 weeks' GA, 91.34%(211 of 230) at 28 to 29 weeks' GA, 97.86%(367 of 375) at 30 to 31 weeks' GA. The incidences of the major morbidities were moderate-to-severe bronchopulmonary dysplasia,16.52% (113 of 671); severe intraventricular hemorrhage and/or periventricular leukomalacia, 2.49%(17 of 671); severe necrotizing enterocolitis , 2.63%( 18 of 671) ; sepsis, 2.34% ( 16 of 671) ; and severe retinopathy of prematurity, 4.55% ( 27 of 593), 65.79% (450 of 671) survived without major morbidities. After adjustment for GA, birth weight, and 5-min Apgar score, antenatal steroid administration(OR = 2.397), antenatal magnesium sulfate administration(OR= 1.554) were the positivity factors to survival without major morbidity of VPIs，however， surfactant therapy (OR= 0.684,), and delivery room resuscitation (OR = 0.626) that were the negativity factors.The present results indicate that survival and the incidence of survival without major morbidities increased with GA. Further, antenatal administration of steroids and magnesium sulfate, surfactant therapy, and delivery room resuscitation were pronounced determinants of survival without morbidities.